JHUM CULTIVATION IN MANIPUR: A CASE STUDY - Laimayum Ashutosh Sharma (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Manipur is one of the important states in the north-eastern part of India with an area of 8621 square miles. About 90% of total area is hill areas and the remaining 10 % valley. Settled agriculture is practised in the valley. Because of the uneven terrain of the hill districts, settled agriculture is impossible. Thus, communities in the said districts have to rely on jhum cultivation for their livelihood. However, this method of cultivation has its own challenges which pose as a hindrance to agricultural production and development. The current article seeks to investigate and examine the present scenario of jhum cultivation in the districts of Chandel, Churachandpur, Senapati, Tamenglong and Ukhrul. The article delves into the status of cultivation, natural as well as man-made challenges face by jhum cultivation. The paper also describes impacts of jhum cultivation on the environment of the said districts and Manipur as a whole. Moreover, it also suggests ways to minimise the impact of jhum cultivation on our environment so that the cultivation method itself as well as resources can be sustainably adopted and utilised.